ANALISIS KEUNTUNGAN PETANI KOPRA DI KECAMATAN TENGAKABUPATEN MINAHASA SELATAN - Christian ., Suherman; Vicky V.J. Palenewen; Arie D.P Mirah (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine whether the business copra in the district Tenga still profitable, to determine what the Break Event Point Tenga copra farmers in the district, and to identify factors - factors that affect business profits copra. The data used are primary and secondary data. Determination of the sample villages in this study using the "purposive sampling" of the sample villages selected intentionally or based on certain considerations that are copra and the village center is easily reached by researchers thus simplifying data retrieval. Data sample is taken from farmers who have land locations above 2 hectares that surround the District Tenga with a sample size of 40 farmers as respondents in the village Tawaang, Radey village, the village of Tenga, Sapa Village, Sapa West Village, and Village of Pakuweru. To answer the first objective used descriptive analysis and profit analysis, ntuk answered the second goal calculate the break even point. Break Even Point and to answer the third goal is to see how the influence of independent variables (independent variables) Xi is a factor of production to the dependent variable (the dependent variable) Y namely profits, used multiple linear regression analysis. Results can be concluded that the copra farmers economically advantageous in the study area, namely in terms of value - average R / C per farmer is 1.80 and the calculation results show that the break-even point copra farmers profitable because pass the impass point. Education, age, dependents, the experience of farmers, land area and the number of coconut palms simultaneously influence no significant effect on earnings copra farmers due to land and businesses copra in the area of research has become a legacy handed down so that the well management system has been implemented by itself while the factors of production cost effect the real income of farmers due to the advantage of copra business is strongly influenced by labor that perform processing of coconut climbing to cultivate coconuts into copra.